Epidemiology of trauma in patients with mental disorders - Sofia M Muns; Ediel O Ramos-Meléndez; Lourdes Guerrios; Pablo Rodríguez-Ortiz (Trauma Surgery & Acute Care Open)
Objectives We aimed to explore the influence of mental disorders on the risk of developing complications and in-hospital mortality after trauma.Methods We conducted an institutional review board-approved cohort study of 23 500 adult patients admitted to the Puerto Rico Trauma Hospital from 2002 to 2019. Participants were divided into 2 groups according to the presence or absence of psychiatric illnesses. Logistic regressions were employed to investigate the effect of mental illness on study outcomes.Results Psychiatric illness was associated with higher risk of complications; this risk increased with age. The pattern was accentuated for those with substance use disorders (SUD) and attenuated for those with non-substance-related diagnoses (NSRD). Psychiatric patients with Glasgow Coma Scale (GCS) scores of 15 had a 42% (95% CI 1.17 to 1.73) higher risk of dying, while the opposite was seen for those with scores <15 (adjusted OR=0.79; 95% CI 0.64 to 0.99). SUD was associated with a 51% (95% CI 1.21 to 1.88) higher risk of death in patients with GCS scores of 15, while NSRD was linked to a 49% (95% CI 0.33 to 0.79) lower odds of death among subjects with scores <15.Conclusions Our results suggest that trauma patients with SUD are at increased risk of developing complications and those with SUD and GCS scores of 15 are at increased risk of death. Mental health screening is an essential component of the management of trauma patients. Stratifying based on mental health disorders may be helpful during the clinical management of trauma patients, as those with SUD may benefit from more aggressive management.Level of evidence Level 4, prognostic and epidemiological study.Study type Original retrospective cohort study.